(untitled) (mathematica didactica, 2017)
Insights that students gain when solving difficult mathematical problems are not always used to solve similar or structurally equal problems. The question arises how general or domain specific these insights into mathematical relationships are or can be. In case studies, the term of domain specificity is theoretically amplified with the help of the term ‘latent structure of sense’ coined by Oevermann et al. and applied to the learning of mathematics by Krumsdorf. The analysis of problem solving processes by abduction theory (Peirce and Meyer) can be complemented by the term of latent structure of sense, as will be shown as well.